Understanding Human Resource Management in Global Industry Practices: Systematic Review of International Publication - PURWATMINI, NINING; ELMIE; PRANOGYO, ANTAIWAN BOWO; SUMAMPOUW, RULAND WILLY JACK; ARIFIN, ANTONI LUDFI (The journal of contemporary issues in business and government, 2021)
Understanding how human resource management is in different contexts is very important. Because the success of an organization in achieving its final goals is closely related to the understanding of HR managers before implementing governance efforts in the field, one of which is applying HR in the international business industry. To understand and apply these human resources, we have done a series of electronic data searches. We focus our search on international publications through data searches based on the Google Scholar application and other electronic data sources that we systematically choose between 2010 and 2021 issues. Then we analyze the data by involving the coding system, evaluation, and in-depth interpretation to get answers to the research questions of this study with valid and reliable findings. HR management is also critical in international business and industrial practices, as is HR in a national context. The difference is that HR management is more stringent in the context of human resources in the international business Process design is highly structured in a company to ensure the successful and productive use of human resources by ensuring that it achieves borderless, territorial, and adaptable goals to all conditions, cultures, and geopolitics.